(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article describes the image of Arstanaly Osmonbekov, who made a huge contribution to the establishment of Soviet power on the Kyrgyz land, and the value of our people